230k views
4 votes
2x - 2y = 6 3x + 2y = 9 Solve the system of equations. A) x = 0, y = 3 B) x = 3, y = 0 C) x = 1, y = -2 D) x = -2, y = 1 E) x = 6, y = 3

User Diarra
by
5.5k points

1 Answer

5 votes

Answer:

There are 2 ways to solve this system: by elimination or by graphing. I will solve it by elimination. First will solve for x.


2x - 2y = 6\\3x + 2y = 9\\\\5x = 15\\\\x = 3\\

Now we will solve for y using what we got for x.


2(3) - 2y = 6\\\\6 - 2y = 6\\\\-2y = 0\\\\y = 0

Solution:

A:
(0, 3)

User Rominus
by
6.5k points